2005
DOI: 10.1634/stemcells.2005-0194
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Features of Primate Embryonic Stem Cells

Abstract: Using flow cytometry measurements combined with quantitative analysis of cell cycle kinetics, we show that rhesus monkey embryonic stem cells (ESCs) are characterized by an extremely rapid transit through the G 1 phase, which accounts for 15% of the total cell cycle duration. Monkey ESCs exhibit a non-phasic expression of cyclin E, which is detected during all phases of the cell cycle, and do not growth-arrest in G 1 after ␥-irradiation, reflecting the absence of a G 1 checkpoint. Serum deprivation or pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
134
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(157 citation statements)
references
References 33 publications
20
134
1
2
Order By: Relevance
“…This pattern of expression of Cyclin E is not unique to nematodes. Cyclin E expression has been shown to be continuous throughout the cell cycle in germline stem cells of Drosophila (23) and embryonic stem (ES) cells from mouse (24) and primates (25). High level of cyclin E was proposed to indicate ''stemness'' of the cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of expression of Cyclin E is not unique to nematodes. Cyclin E expression has been shown to be continuous throughout the cell cycle in germline stem cells of Drosophila (23) and embryonic stem (ES) cells from mouse (24) and primates (25). High level of cyclin E was proposed to indicate ''stemness'' of the cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…One of the explanations for the high aneuploidy rate in hESCs cells, compared with hiPSCs and controls, might lies in the possibility that ESCs guarantee rapid cell division by bypassing certain mechanisms of cell-cycle control and by that, enabling the survival of chromosomally aberrant cells. As it turns out, in early development, the strict requirements for cell growth are suspended to allow rapid cell proliferation 38,39 and is activated again when ESCs are induced to differentiate into embryoid bodies. 40,41 A recent study, conducted by Mayshar et al 34 , identified a substantial number of hiPS cell lines carrying full and partial chromosomal aberrations.…”
Section: Aneuploidy Screeningmentioning
confidence: 99%
“…Although the short G1 and extended S-phase are also observed in murine, nonprimate, and primate ESC [6,7], the G1 to S transition seems to be subject to species-specific regulation [5].…”
Section: Introductionmentioning
confidence: 97%